Citizen-centric smart city strategies: Analyzing public demand and economic value in South Korea - Kim, Kyungah; Seung, Hyunchan; Kim, Jinseok; Kim, Junghun (Cities, 2025)
Smart cities are gaining attention as a solution to various urban challenges through improvements in energy efficiency and transportation systems. To ensure sustainability, a smart city must be designed to meet the needs of its service users. This study analyzed citizens' preference structure for smart cities using the discrete choice methodology. Given the public goods nature of smart city policies, the contingent valuation method was also applied. The results indicate that, on average, citizens support the development of smart cities, with preferences ordered as follows: smart energy, buildings, transportation, and healthcare. It was also found that the citizens priorities in smart city sectors differ from those of the government as the provider. Furthermore, citizens perceive reductions in carbon dioxide emissions as a significant benefit of smart cities. A 10 % reduction in carbon dioxide emissions results in an increase in utility comparable to that of a 15-min reduction in commuting time. •Analyzed public preferences and willingness to pay for smart city services in Korea•Citizens preferred smart city construction and most preferred transportation sector.•Identified a gap between citizen priorities and government-led smart city projects•Citizens highly valued CO₂ reductions, equating 10 % cuts to 15-min shorter commutes.•Suggested optimal smart city policy directions reflecting citizens' economic values